الشعر العربي في خدمة المجتمع والاقتصاد الوطني: شعراء ولاية أدماوا أنموذجا = The Islamic values in the poetry of the Guinean Poet Mohamed Lamine Diaby: a descriptive and analytical study - Umar, Aliyu Pariya; Hussein, Nasr El Din Ibrahim Ahmed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
الشعر تسجيل وتوجيه لمظاهر الحياة، ومشاعر المجتمع، ووسيلة لتصوير جوانب حياة كل أمة، والشاعر ابن بيئته حسب المقولة المشهورة، وذلك أنه من طبيعة الشعر أن يعالج الحياة الاجتماعية على اختلاف أنواعها، ومن أخطر هذه الجوانب؛ الجانب الاقتصادي للأمة، إذ إنه هو عمود الحياة، وقوامها، فهذه الورقة محاولة كشف إسهامات بعض شعراء ولاية أدماوا في خدمة الاقتصاد الوطني، حثاًّ على العمل والمثابرة والتقوى، وتصوير الإنفاق في خدمة المجتمع في قوالب أدبية ممتعة، وأساليب فنية رائعة، مما له أثر إيجابي في تشجيع المواطنين على الاقتداء في الجانب الفني، والتجاري، والمهني على السواء. ********************************************************* Poetry is writing about and guiding the phases of life and feelings of society. In addition, it is viewed as a medium to portray various dimensions of life of every society. As per the famous adage, a poet is the son of environment which means that nature of poem is to deal with the various aspects of social life. Likewise, economical aspect is highly vital of social life given that economy is the pillar and strength of any nation. The purpose of this paper is to unveil the contributions of some poets of Adamawa state in terms of the service of the national economy. Employing the exciting literary models and brilliant artistic styles, they urged people to work and to be steadfast and pious, especially to spend money for the service of society. Their efforts have a positive impact in encouraging citizens to excel in the technical, commercial and professional milieus.